LESIONS ON THE SOFT PALATE CAUSED BY ORAL SEXUAL INTERCOURSE: A CASE REPORT - Bjekic, Milan; Ivanovski, Kiro (HEALTH CARE, 2021)
Background/Aim: Oral sex is a common practice in sexually active people of all ages, including teenagers and can be accompanied by sexually transmitted infections and trauma of the oral or genital region. The aim of this study was to present the lesions on the soft palate that occurred after receptive oral sexual intercourse. Case report: We present a 17-year-old student with fellatio-associated purpuric lesions on the soft palate, which disappeared spontaneously within ten days. Conclusions: Dental care professionals should be aware that petechial oral lesions may result from sexual intercourse and data on oral sex practice should always be taken.